Health literacy in adolescents and young adults in Benin: French translation and validation of the health literacy measure for adolescents (HELMA) - Ikediashi, Bonaventure G.; Ehrmann, Cristina; Michel, Gisela (Frontiers in Psychology, 2024)
Background The Health Literacy Measure for Adolescents (HELMA) is a self-assessment validated tool used to measure health literacy in adolescents. This study aims to evaluate the psychometric properties of the French translation of the Health Literacy Measure for Adolescents (F-HELMA). Methods The HELMA questionnaire was translated according to the World Health Organization's (WHO) recommendation for translation and adaptation of instruments. It was pre-tested with 30 students. Subsequently, 495 adolescents and young adults from five senior secondary high schools in Benin completed the questionnaire. A sample of 44 participants completed the questionnaire twice over a 2-week period to determine the test-retest reliability. Construct validity was evaluated using confirmatory factor analysis (CFA) and convergent validity was analyzed the Health Literacy Assessment Tool. Results and discussion The F-HELMA—French translation of the Health Literacy Measure for Adolescents, showed moderate to good psychometric properties. CFA showed good fit indices for a seven-factor model. Reliability figures fell within an acceptable range; Cronbach's alpha ranged from 0.64 (moderate) to 0.89 (good) across the different subscales, and the intraclass coefficient (ICC) ranged from 0.82 to 0.96, indicating good test-retest reliability. Pearson correlation with HLAT-8 showed good convergent validity (r = 0.54, p < 0.001). This study provides support for the use of the F-HELMA, as a valid and reliable instrument to measure health literacy in adolescents and young adults in West African French speaking countries.